2021
DOI: 10.3390/mi12070763
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Flow Distribution of Complex Micron Scale Pipe Network

Abstract: A fluid simulation calculation method of the microfluidic network is proposed as a means to achieve the flow distribution of the microfluidic network. This paper quantitatively analyzes the influence of flow distribution in microfluidic devices impacted by pressure variation in the pressure source and channel length. The flow distribution in microfluidic devices with three types of channel lengths under three different pressure conditions is studied and shows that the results obtained by the simulation calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, Jbeili and Zhang [ 6 ] examined the convective heat transfer performances of flows through porous materials, and found that, in addition to the porosity, the aspect ration of the microscopic porous structure and the possible interfacial thermal resistance can also affect the macroscopic thermal performance of the porous media. For an efficient evaluation of the flow and pressure distributions in a microchannel network, Zhao et al [ 7 ] introduced an electric circuit analogy and applied it to study the effect of microchannel length on the flow behaviors. Another interesting study is presented by Huang et al [ 8 ], where the immersed boundary method has been combined with the lattice Boltzmann method to study the trajectory of a neutrally buoyant circular particle in the pulsatile channel flow.…”
mentioning
confidence: 99%
“…On the other hand, Jbeili and Zhang [ 6 ] examined the convective heat transfer performances of flows through porous materials, and found that, in addition to the porosity, the aspect ration of the microscopic porous structure and the possible interfacial thermal resistance can also affect the macroscopic thermal performance of the porous media. For an efficient evaluation of the flow and pressure distributions in a microchannel network, Zhao et al [ 7 ] introduced an electric circuit analogy and applied it to study the effect of microchannel length on the flow behaviors. Another interesting study is presented by Huang et al [ 8 ], where the immersed boundary method has been combined with the lattice Boltzmann method to study the trajectory of a neutrally buoyant circular particle in the pulsatile channel flow.…”
mentioning
confidence: 99%